2013
DOI: 10.1111/iwj.12028
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of complex traumatic and surgical wounds with a foetal bovine dermal matrix

Abstract: A foetal bovine dermal repair scaffold (PriMatrix, TEI Biosciences) was used to treat complex surgical or traumatic wounds where the clinical need was to avoid skin flaps and to build new tissue in the wound that could be reepithelialised from the wound margins or closed with a subsequent application of a split-thickness skin graft (STSG). Forty-three consecutive cases were reviewed having an average size of 79·3 cm(2) , 50% of which had exposed tendon and/or bone. In a subset of wounds (44·7%), the implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…FBC has been shown to result in 80% graft take of complex traumatic surgical wounds with subsequent STSG placement. 68 Unlike Integra, it has been shown to result in wound healing without STSG in a patient with mixed full-and partialthickness burn. 69 Of note, the burn wound in this study was assessed clinically as a full-thickness burn; however, subsequent biopsies revealed that there was a mixture of full-and partial-thickness burns in the wound bed.…”
Section: Dermal Substitutesmentioning
confidence: 99%
“…FBC has been shown to result in 80% graft take of complex traumatic surgical wounds with subsequent STSG placement. 68 Unlike Integra, it has been shown to result in wound healing without STSG in a patient with mixed full-and partialthickness burn. 69 Of note, the burn wound in this study was assessed clinically as a full-thickness burn; however, subsequent biopsies revealed that there was a mixture of full-and partial-thickness burns in the wound bed.…”
Section: Dermal Substitutesmentioning
confidence: 99%
“… 5 To increase successful ingrowth of the skin graft, this is usually performed in a staged procedure in combination with negative-pressure wound therapy. 6 Hereby, the ADM is transplanted, and negative-pressure wound therapy is performed for several days to improve vascularization of the ADM before skin transplantation. Despite good functional and aesthetic results, this approach is time consuming and cost intensive.…”
Section: Discussionmentioning
confidence: 99%
“…The combination therapy of unmeshed artificial dermis and NPWT has been reported to be effective in the treatment of chronic ulcers and complex wounds with exposed tendon or bone . However, meshed artificial dermis would be suitable, especially in complex wounds, because wound exudates and haematoma could be drained from the fenestration . As for the mechanism involved in the combination therapy with artificial dermis and NPWT in vitro, Baldwin et al reported that continuous negative pressure stimulates the migration and proliferation of human microvascular endothelial cells cultured on artificial dermis through the fenestration of the silicone layer .…”
Section: Discussionmentioning
confidence: 99%